Optimizing Zakat Management in National Economic Recovery in Central Kalimantan - Syaikhu Syaikhu; Rafik Patrajaya (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
This research is motivated by the efforts made by the National Zakat Agency (Baznas) to manage zakat productively to achieve economic prosperity. Zakat funds at Baznas are quite substantial, both at the Regency/City, Provincial, and National levels. If these zakat funds are only distributed for consumption to those entitled to receive them, poverty will certainly never be minimized, let alone eliminated. As long as zakat funds are only distributed for consumption, the objectives of the zakat mandate will never be achieved. The focus of this research is to delve deeper into the strategic steps taken by Baznas to optimize national economic recovery, particularly in Central Kalimantan. This research is empirical (file research), examined using a socio-legal approach to provide a more holistic view of legal phenomena in society. The results of this study indicate that zakat management in Central Kalimantan itself in supporting national economic recovery is divided into two methods. First, zakat management remains classical, primarily for consumption, aimed at meeting the basic needs of those entitled to receive it, such as basic necessities and the Baznas (National Zakat Agency) housing renovation program. Second, zakat is managed productively each year to ensure continued growth, although it does not yet utilize a revolving fund system that could provide additional capital for productive businesses. Optimizing this system is expected to achieve prosperity, well-being, and social justice.